Reproductive strategies and chromosomal aberrations affect survival in the Rivuliid fish Hypsolebias sertanejo - Evangelista, Mariana Machado [UNESP]; Romagosa, Elizabeth; Siqueira-Silva, Diogenes Henrique; Yasui, George Shigueki; Fujimoto, Takafumi; Senhorini, Jose Augusto (Cambridge Univ Press, 2021)
Rivulidae comprises a family of fish largely distributed in Brazil that includes 201 species, of which 125 are considered endangered. This fact emphasizes the need for development of conservation strategies including studies on genetics and reproduction. In this paper, we describe aspects of biology and reproduction of the rivuliid species Hypsolebias sertanejo. We outline the reproductive behaviour of this species under laboratory conditions, analyze ploidy status by flow cytometry, describe reproductive behaviour and performance and test dry and wet incubation of eggs. Although H. sertanejo showed well known patterns of reproductive behaviour, we verified many peculiarities inherent to its reproductive biology. As expected, most individuals were diploid (87.71%), however 14.29% were considered mosaics. Although no sterility was observed within mosaics, infertility of these fish was not fully evaluated. Hatching rate of the eggs collected was very low following both dry and wet incubation (5.04 and 3.79%, respectively). These results provide interesting information regarding the reproductive success of this species, and suggest that chromosomal abnormalities described may reduce the survival of H. sertanejo under natural conditions, limiting the perpetuation of this species, and emphasizing the need for more preservation efforts, including artificial propagation and gene banking.
Keywords: Biotechnology; Fish biology; Fish preservation; Mosaicism; Reproduction